WHEN HYPERTENSION “BLOWS AWAY ” – A CASE REPORT OF RENAL ARTERY ESTENOSIS - Midões, Carolina (2023)
Secondary arterial hypertension (HTN), arises as a consequence of potentially treatable conditions, has an estimated prevalence of 5-10% in the hypertensive population. Approximately 85% cases are amongst individuals aged 40 and younger. The most common secondary etiologies vary by age group, with transversal renal parenchymal disease being present in all of them. Arterial hypertension of renal origin can be the result of renovascular causes (renal artery stenosis, arteritis, or extrinsic renal artery compression) or renal parenchymal disease. We present a case of a 26-year-old man, with history of tobacco use, diagnosed with grade 3 HTN made during occupational screening, without associated symptoms. The physical exam identified a murmur over the left lumbar region. The initial laboratorial and imaging study was negative, but the axial computed tomography angiography of the abdomen revealed the presence of significant stenosis of the left renal artery. This case demonstrates the importance of investigating suspected secondary hypertension, even in the absence of clinical symptoms. Renal artery stenosis has treatment and its early detection can drastically change long-term prognosis.